Identifying Counterfeit Cigarettes Using Environmental Pollen Analysis: An Improved Procedure*. Issue 6 (17th August 2020) - Chan, Tiffany; Robinson, Guy; Liu, Jonathan; Kurti, Marin; He, Yi; von Lampe, Klaus
Abstract: Traditional pollen preparation techniques provide clear residues for pollen identification; however, such methods are time‐consuming, requiring repeated centrifugation, heating, and digestion with high‐concentration hazardous chemicals. Tobacco leaves can effectively trap environmental pollen due to hairy surface and terpene‐rich exudates. A new tobacco sample processing method was developed by using different extraction chemistry with surfactant. Marlboro Gold cigarettes were employed as model samples for method development. Parameters critical for pollen extraction, which include number of cigarette sticks used, extraction solution, and extraction temperature, were optimized. By using 1% dishwashing detergent to treat three cigarettes at room temperature, the improved method was able to recover sufficient pollen for microscopic analysis in three repeated centrifuge‐washing steps and omit hazardous chemicals involved in traditional methods. We focused on the pollen of common ragweed ( Ambrosia artemisiifolia ), a plant native to North America, as an indicator to differentiate genuine and counterfeit U.S. brand cigarettes. Results from analyzing randomly purchased genuine (authenticated by forensic examination) and known counterfeit Marlboro Gold provided by law enforcement revealed that a significant amount (39%) of Ambrosia were consistently present in all genuine samples, while counterfeit contained none or only trace count. Similar results were found in other counterfeit U.S. brand cigarettes (all seized in the U.S.) involved in this study as well. Lack of Ambrosia in cigarette strongly indicates the product was not originated in the United States.